PTU-035 Immunologic responses to hookworm infection in Crohn's disease. (23rd September 2015) - Meran, L; Blount, D; Hooi, D; Alan, B; Subramanian, V; Pritchard, D; Hawkey, C J; Fortun, P
Abstract : Introduction: Helminths such as hookworms survive by modulating host immune responses as a strategy to escape the host's defence mechanisms.1 Hookworm infection is demonstrated by a polarised Th2 response, releasing characteristic cytokines (IL-4, IL-5, IL-10, IL-13). Conversely, Crohn's disease is characterised by a Th1 response, releasing pro-inflammatory cytokines (TNF, IFN, IL-2)2 . The reciprocal inhibition of cytokine products between distinct T helper cell responses, has led to studies of hookworms as adjuncts to immunosuppressants in Crohn's disease.2 The Nottingham Digestive Diseases Centre recently completed a placebo-controlled trial on the effect of hookworms on disease activity in Crohn's disease, providing an opportunity to study changes in T cell populations. Methods: Blood samples were obtained at four time points during the trial. Hookworm specific IgG was measured using ELISA methodology and confirmed by Western blot analysis. Cytokine ELISAs were carried out on IL-4, IL-5, IL-10, TNF, IFN and IL17. Regulatory T cells were measured by flow cytometry utilising CD4, CD25 and Foxp3 antibodies. Results: Hookworm infection was indicated by the presence of IgG–reactive 33-kDa bands on Western Blots, and was confirmed by an eosinophilia and positive faecal egg counts. Cytokine ELISAs demonstrated a statistically significant increase in IL5 in the intervention group. After 6 weeks of inoculation with hookworm larvae, the mean IL5 increase from baseline in the intervention group was 515% compared to 90% in controls. Trends of reduced levels of TNF and IL-17 were observed alongside increased levels of IL-10 in the intervention group. Patients on azathioprine and steroids were found to have significantly lower IFN and IL-10 levels compared to patients not on these drugs. Conclusion: Successful establishment of hookworms in patients with active Crohn's disease is haematologically demonstrated by a heightened eosinophilic response, and supported by Western Blot analyses and faecal egg counts. Raised IL-5 levels in patients treated with hookworms also suggest a switch to an anti-helminthic Th2 response. Insights into possible collaborative effects of hookworms and immunosuppressive drugs have been demonstrated. Individual patient cytokine profiles will be correlated against CDAI scores in order to clarify whether the Th2 response confers benefits in Crohn's disease.